Changes in High-sensitivity C-reactive Protein Levels after Laparoscopic Gastric Stapling Procedures versus Laparoscopic Gastric Banding. Issue 10 (October 2014) - Gebhart, Alana; Young, Monica; Villamere, James; Shih, Anderson; Nguyen, Ninh T.
Obesity, hypertension, diabetes, and hyperlipidemia are risk factors for the development of coronary artery disease. High-sensitivity C-reactive protein (hs-CRP) is an inflammatory biomarker that has been shown to be an independent predictor for cardiovascular risk. The aim of the current study was to examine the changes in cardiovascular risk profile in morbidly obese patients who underwent laparoscopic gastric stapling procedures (bypass and sleeve) compared with laparoscopic gastric banding. Levels of hs-CRP were measured preoperatively and at 12 to 24 months post-operatively. Based on hs-CRP levels, cardiovascular risk was categorized as low (less than 1 mg/L), moderate (1 to 3 mg/L), or high (greater than 3 mg/L). A total of 52 patients underwent gastric stapling procedures and 49 underwent gastric banding and both had preoperative and postoperative hs-CRP levels measured. There were no significant differences in age, gender, or preoperative body mass index (BMI) between groups. At baseline, 48.0 per cent of patients undergoing gastric stapling and 38.8 per cent of patients undergoing gastric banding had moderate or high cardiovascular risk. BMI at 24 months was significantly lower in the gastric stapling compared with the gastric banding group (30.4 ± 5.4 vs 36.1 ± 5.5 kg/m 2, respectively, P < 0.01). Of the patients with elevated cardiovascular risk, 64.0 per cent of gastric stapling versus 57.8 per cent of gastric banding patients had a reduction in risk category at 12 to 24 months follow-up, whereas 1.9 per cent of patients undergoing gastric stapling versus 4.1 per cent of patients undergoing gastric banding had an increase in risk category. The mean reduction in hs-CRP level for patients with elevated cardiovascular risk was greater for gastric stapling compared with gastric banding procedures (-1.10 ± 0.94 mg/L vs -0.67 ± 0.82 mg/L, respectively, P < 0.05). Cardiovascular risk improved in the majority of patients after bariatric surgery, but a more pronounced improvement occurred in patients who underwent gastric stapling procedures.